Mesoporous CuCo2O4 nanograsses as multi-functional electrodes for supercapacitors and electro-catalysts1. Issue 18 (14th May 2015) - Cheng, Jinbing; Yan, Hailong; Lu, Yang; Qiu, Kangwen; Hou, Xiaoyi; Xu, Jinyou; Han, Lei; Liu, Xianming; Kim, Jang-Kyo; Luo, Yongsong
<x xml:space="preserve">Abstract</x> A freestanding mesoporous CuCo2O4 nanograss electrode exhibits a superior pseudocapacitive performance and a high electrocatalytic activity towards methanol oxidation.